Baduanjin exercise in the treatment of hypertension: A systematic review and meta-analysis - Ma, Zhen; Lei, Honghui; Tian, Kexin; Liu, ZhiZe; Chen, Ying; Yang, Haoqi; Zhu, Xiangyu (Frontiers in Cardiovascular Medicine, 2022)
Abstract Background: As a therapy to prevent and treat hypertension,exercise is increasingly widely used in clinical practice.But Baduanjin as a relaxed and convenient mode of exercise, is not recommended by professional health organizations to treat hypertension. The purpose of this article is to examine the efficacy of Baduanjin as an antihypertensive exercise therapy. Methods:Our systematic retrieve of the entire relevant literature in 12 databases, which finally included 28 qualified trials involving Baduanjin intervention for hypertension,After a quality evaluation and risk of bias assessment of the included trials, pre-and post-intervention BP values in these trials were extracted and a meta-analysis of the random effects results was performed,To explore the factors influencing BP reduction, we also performed a subgroup analysis of the results. Results:Participants (n=2121) were mostly middle-aged adult (61.74±5.85years of age, mean ± SD), with baseline blood pressure (systolic blood pressure (SBP) =150.7 ± 9.2 mmHg, diastolic blood pressure (DBP)=93.2±8.8mmHg).Baduanjin practiced for an average of 7.5 ± 3.8 sessions / week, 28.2 ± 12.8 min /session, and 16.7 ± 9.2 weeks..Overall, Baduanjin resulted in SBP(-9.3mmHg,d=-1.49,95%CI:-1.73--1.13) and DBP(-6.3mmHg,d=-1.20,95%CI:-1.51--0.88), vs the control group (p <0.001) was significantly lower.In the subgroup analysis, SBP heterogeneity was significantly reduced in the older group. Conclusion:Our results ndicate that Baduanjin can effectively reduce blood pressure (Reduction of SBP and DBP by-9.3mmHg and-6.3mmHg), thus reducing the morbidity of cardiovascular grade in hypertensive patients, which is more suitable for its application in the elderly population.